International diversification in a correlated world - Heiberg, Ove Gilje (2020)
In this paper I look at the correlation between developed and emerging markets, arguing that the increased correlation has reduced the potential benefits of international diversification. Furthermore, I look at markets that still seem to be highly uncorrelated to developed markets, and how to more efficiently include these in a global portfolio. By ranking emerging markets based on their 12 month rolling correlation coefficient to the MSCI World Index, the country weightings are determined. A global portfolio with different constraints is then created to demonstrate that investors can boost risk adjusted performance by using a more selective correlation based investment approach.